أثر مخرجات الابتكار على النمو الاقتصادي في الدول العربية خلال الفترة (0122-2020) دراسة قياسية باستخدام نماذج بانل - روبحي, مايسة; هدروق, أحمد (The impact of innovation outputs on economic growth in Arab countries during the period (2012-2020) Standard study using panel models, 2022)
هدفت هذه الدراسة إلى قياس أثر مخرجات الابتكار (الإبداعية، المعرفية والتكنولوجية) على النمو الاقتصادي في عينة من الدول العربية خلال الفترة (2012-2020)، باستخدام نماذج بانل. وخلصت الدراسة إلى أن النموذج الأفضل لتقدير نموذج بانل الساكن في دراستنا هو نموذج التأثيرات الثابتة، كما بينت النتائج وجود تأثير سلبي ومعنوي للمخرجات الإبداعية ومؤشر خلق المعرفة على النمو الاقتصادي، ووجود تأثير إيجابي ومعنوي لمؤشر تأثير المعرفة على النمو الاقتصادي. This study aimed is to investigate the impact of innovation outputs (creative, knowledge and technology) on economic growth in the Arab countries during the period (2012-2020), using static panel models.. The study concluded that the best model for estimating the static panel model in our study is the fixed effects model. The results also showed a negative and significant effect of creative outputs and the knowledge creation index on economic growth, and a positive and significant impact of the knowledge impact indicator on economic growth.
مقال
Keywords: مخرجات الابتكار ; المخرجات الإبداعية ; المخرجات المعرفية والتكنولوجية ; نماذج بانل الساكن